De-alloyed PtCu/C catalysts with enhanced electrocatalytic performance for the oxygen reduction reaction. Issue 32 (9th August 2021) - Xiao, Zhuojie; Wu, Hao; Zhong, Huichi; Abdelhafiz, Ali; Zeng, Jianhuang
Abstract : After electrochemical de-alloying, PtCu/C catalyst with a rich Pt shell demonstrated an enhanced ORR activity and superior durability. Abstract : In electrochemical reactions, interactions between reaction intermediates and catalytic surfaces control the catalytic activity, and thereby require to be optimized. Electrochemical de-alloying of mixed-metal nanoparticles is a promising strategy to modify catalysts' surface chemistry and/or induce lattice strain to alter their electronic structure. Perfect design of the electrochemical de-alloying strategy to modify the catalyst's d-band center position can yield significant improvement on the catalytic performance of the oxygen reduction reaction (ORR). Herein, carbon supported PtCu catalysts are prepared by a simple polyol method followed by an electrochemical de-alloying treatment to form PtCu/C catalysts with a Pt-enriched porous shell with improved catalytic activity. Although the pristine PtCu/C catalyst exhibits a mass activity of 0.64 A mg −1 Pt, the dissolution of Cu atoms from the catalyst surface after electrochemical de-alloying cycling leads to a significant enhancement in mass activity (1.19 A mg −1 Pt ), which is 400% better than that of state-of-the-art commercial Pt/C (0.24 A mg −1 Pt ). Furthermore, the de-alloyed PtCu/C-10 catalyst with a Pt-enriched shell delivers prolonged stability (loss of only 28.6% after 30 000 cycles), which is much better than that of Pt/C with a loss of 45.8%. By virtue of scanning transmission electron microscopy and elemental mapping experiments, the morphology and composition evolution of the catalysts could clearly be elucidated. This work helps in drawing a roadmap to design highly active and stable catalyst platforms for the ORR and relevant proton exchange membrane fuel cell applications.